2019
DOI: 10.3390/ijms20133248
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Stimulation Alleviates CFA-Induced Inflammatory Pain Via Suppressing P2X3 Expression

Abstract: Chronic inflammatory pain is one of the most common complaints that seriously affects patients’ quality of life. Previous studies have demonstrated that the analgesic effect of electroacupuncture (EA) stimulation on inflammatory pain is related to its frequency. In this study, we focused on whether the analgesic effects of EA are related to the period of stimulation. Purinergic receptor P2X3 (P2X3) is involved in the pathological process underlying chronic inflammatory pain and neuropathic pain. We hypothesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 42 publications
0
56
0
Order By: Relevance
“…Electroacupuncture (EA) is widely used to treat chronic pain, including diabetes-associated pain [26][27][28]. Mounting evidence in animal models indicates involvement of P2X3 receptor in neuropathic pain [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Electroacupuncture (EA) is widely used to treat chronic pain, including diabetes-associated pain [26][27][28]. Mounting evidence in animal models indicates involvement of P2X3 receptor in neuropathic pain [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Related studies have shown that the therapeutic effect of EA on pain is closely related to its intervention in the peripheral nervous systems. [32][33][34] A previous study demonstrated that the therapeutic effect of EA on chronic pain is partially achieved by regulating the PKCε signal transduction pathway. 35,36 EA can also exert its analgesic effect by regulating the expression of mGluR5 in the DRG.…”
Section: Introductionmentioning
confidence: 99%
“…It was noted that 100 Hz EAP stimulation had a stronger effect than stimulation with 2 Hz. In addition, EAP reversed the increased P2X3R-immunoreactivity and protein expression in DRGs, as measured by quantitative immunohistochemistry and western blotting, respectively [44,45].…”
Section: P2x3 Receptorsmentioning
confidence: 92%
“…When the PWT and PWL were measured with mechanical pressure and heat, respectively, on the CFA-treated hind paw of rats, EAP applied to Zusanli and BL60 (Kunlun acupoint) exerted analgesia in this inflammatory pain model [44,45]. It was noted that 100 Hz EAP stimulation had a stronger effect than stimulation with 2 Hz.…”
Section: P2x3 Receptorsmentioning
confidence: 99%